Antimicrobial susceptibility pattern of extended-spectrum beta- lactamase producing Klebsiella pneumoniae clinical isolates in an Indian tertiary hospital - Amit Kumar Singh; Sonali Jain; Dinesh Kumar; Ravinder Pal Singh; Hitesh Bhatt (Wolters Kluwer Medknow Publications, 2015)
Objective: There is an increased prevalence of extended-spectrum beta-lactamase producing Klebsiella pneumoniae (ESBL-KP) worldwide including India, which is a major concern for the clinicians, especially in intensive care units and pediatric patients. This study aims to determine the prevalence of ESBL-KP and antimicrobial sensitivity profile to plan a proper hospital infection control program to prevent the spread of resistant strains. Methods: KP isolates obtained from various clinical samples were evaluated to detect the production of ESBL by phenotypic methods. Antimicrobial susceptibility profile was also determined of all the isolates. Findings: Of 223 nonduplicate isolates of K. pneumoniae, 114 (51.1%) were ESBL producer and antimicrobial susceptibility profile showed the isolates were uniformly sensitive to imipenem and highly susceptible to beta-lactamase inhibitor combination drugs (67-81%) and aminoglycosides (62-76%), but less susceptible to third generation cephalosporins (14-24%) and non-β-lactam antibiotics such as nitrofurantoin (57%), fluoroquinolones (29-57%), piperacillin (19-23%), and aztreonam (15-24%). Conclusion: This study found that beta-lactamase inhibitor combinations are effective in treatment of such infections due to ESBL-KP thus these drugs should be a part of the empirical therapy and carbapenems should be used when the antimicrobial susceptibility tests report resistance against inhibitors combinations.